Klasifikasi Penyakit Chronic Kidney Disease (CKD) Dengan Menggunakan Metode Extreme Learning Machine (ELM) - Ivan Fadilla; Putra Pandu Adikara; Rizal Setya Perdana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Kidneys are important organs that are focussed on maintaining blood composition by preventing accumulation of waste and controlling fluid balance in the body. Chronic Kidney Disease (CKD) is one of the diseases of the kidneys caused by infection in the kidney and also the blockage caused by kidney stones. In this case medical personnel and experts are still not maximized in classifying CKD disease, the authors apply the method of Extreme Learning Machine (ELM) on the problem of classification of CKD disease. ELM is one method of artificial neural network classification that has a fast learning speed and based on previous research has a good accuracy value compared with existing methods in artificial neural networks. In this research got comparison of data of train and optimal test data with ratio 70:30 and amount of hidden neuron counted 50 hidden neuron accuracy value equal to 96,7%. It can be concluded that the method of Extreme Learning Machine (ELM) is quite well implemented for the classification process of Chronic Kidney Disease (CKD) disease.